Encontros de olhares : ensaiando carto(foto)grafias com usuários de drogas - Guedes, Lidiane de Fátima Barbosa (2014)
In the contemporary scenario of the capitalistic Western societies, the flashes of media photographers coupled with legal and scientific hegemonic discursive productions, give light to the body of drug users. Production of photographic image of the infamous subject, provided body - drugged body that contrasts with the other clichés enunciator´s images of beautiful, healthy and perfect body to be consumed. From the web of clichés of contemporary images, this Master thesis was composed with other strands of this web imagery, in order to compose looks, bodies and becoming deviations with said subject infamous drugged bodies. Toward this goal, we conducted meetings with drug users and other residents of a municipality in the Recôncavo of Bahia. Encounters with drug users (crack, marijuana and alcohol) were guided by the proposed production of photographs taken by the user of drugs. The first steps of rapprochement with partners followed the direction: shooting from what was important in their lives, but in time, we deviate from the risk of the web of representation and not confrontational images, which could favor this proposal, and let us guided by other track tensioning of clichés images: producing images from the user´s own relationship with drugs. The body - stoned in the crosshairs of photography and ´look like´, current look / virtual. To follow the process of composition looks and experimentation of thought with partners this study, we invested in mapping as a method of intervention research. The technological feature of the camera founds carto(foto)grafia, subjectivity device, producing cracks in the lenses pointing stereotyped ways of producing and viewing pictures of drug users. In the composition of the theoretical, were affected by the traces of the thinking of philosophers of difference, Baruch Spinoza, Gilles Deleuze, Félix Guattari, Michel Foucault, Friedrich Nietzsche and the like.